Development of an Assessment Instrument for Students Discipline and Responsibility in Physics Practicum-Based Cooperative Learning - Ningsih, Novi Tri Rahayu; Rosidin, Undang; Viyanti, Viyanti; Distrik, I Wayan; Abdurrahman, Abdurrahman (STMIK Widya Cipta Dharma, 2025)
This This study aimed to develop a valid, reliable, and practical assessment instrument to measure students’ discipline and responsibility in Jigsaw-type cooperative learning based on physics practicum. The research used the Research and Development (R&D) method with development steps adapted from Borg & Gall, involving expert validation, field trials, and statistical analysis. Expert validation indicated high validity scores (87.0% for discipline, 94.7% for responsibility). The instrument was tested on 30 students, and reliability scores (Cronbach’s alpha) were 0.70 (discipline) and 0.92 (responsibility), indicating good to very high reliability. Practicality scores averaged 90.72 and 91.80, respectively, based on teacher feedback, reflecting ease of use and usefulness. The results confirm that the developed instrument is suitable for implementation in physics learning to help teachers monitor and foster character development effectively. This research also contributes significantly to educational assessment tools aligned with the Merdeka Belajar framework and the Pancasila Student Profile, offering a foundation for future enhancements and broader application in other subjects and competencies. Additionally, the integration of character education within collaborative learning environments ensures a more holistic approach to student development. The findings suggest that systematic assessment instruments are essential in supporting teachers to objectively measure affective skills, which are often overlooked in traditional classroom assessments.